Tensile properties and die swell behaviours of highly filled polypropylene nanocomposites. (7th February 2020) - Lin, Xiang; Wu, Chang-Qing; Ren, Dong-Yun
ABSTRACT: Highly filled polypropylene (PP) composites incorporated with zero-, one- and two-dimensional nanofillers (0D, 1D and 2D, NFs) were investigated through measuring tensile properties and extrudate swell behaviour. Effects of NFs concentration and particle dimensionality on die swell ratio and tensile properties were identified under the given melt pressure, temperature and shear rate. A static extensional flow mixer with contractional flow gaps was used to improve the dispersion of NFs. Results showed that enhanced tensile properties of PP/NFs were achieved by employing such a mixer. The extrudate swell ratio of the as-prepared PP/NFs was found to exponentially increase with shear rate, linearly increase with melt pressure while linearly decrease with melt temperature. The confining efficiency of particle dimensionality on extrudate swell degree could be ranked from strongest to weakest as 2D (flake), 1D (rod) and 0D (sphere).